2023
DOI: 10.7554/elife.75631
|View full text |Cite
|
Sign up to set email alerts
|

NPAS4 in the medial prefrontal cortex mediates chronic social defeat stress-induced anhedonia-like behavior and reductions in excitatory synapses

Abstract: Chronic stress can produce reward system deficits (i.e., anhedonia) and other common symptoms associated with depressive disorders, as well as neural circuit hypofunction in the medial prefrontal cortex (mPFC). However, the molecular mechanisms by which chronic stress promotes depressive-like behavior and hypofrontality remain unclear. We show here that the neuronal activity-regulated transcription factor, NPAS4, in the mPFC is regulated by chronic social defeat stress (CSDS), and it is required in this brain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 101 publications
(156 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, FRMPD3 is an NPAS4-regulated inhibitory neuronal gene, suggesting that the activity of FRMPD3 promotes the development of excitatory synaptic connections in somatostatin neurons [ 70 ]. Several studies have suggested that NPAS4 may regulate depression, anxiety, and neurocognitive disorders and play a critical role in the correlation between long-term stress and symptoms of depression [ 71 , 72 ]. Our analysis suggests that FRMPD3 is involved in synaptic formation and regulation, potentially influencing MDD development by modulating synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FRMPD3 is an NPAS4-regulated inhibitory neuronal gene, suggesting that the activity of FRMPD3 promotes the development of excitatory synaptic connections in somatostatin neurons [ 70 ]. Several studies have suggested that NPAS4 may regulate depression, anxiety, and neurocognitive disorders and play a critical role in the correlation between long-term stress and symptoms of depression [ 71 , 72 ]. Our analysis suggests that FRMPD3 is involved in synaptic formation and regulation, potentially influencing MDD development by modulating synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, an important question is whether similar homeostatic mechanisms based on experience-induced transcription maintain the functional stability of neural circuits other than the visual cortex. Given that experience-induced gene transcription was observed in many neural circuits 33,34,36,[81][82][83][84][85] and that experiments e.g in the hippocampus, the prefrontal cortex and the somatosensory cortex revealed that early-induced TFs such as NPAS4 48,86,87 and FOS 65 and late-induced effectors such as ARC 88 , NARP 53 and BDNF 51 regulate specific sets of synapses and E/I-ratio according to a homeostatic circuit logic also in these neural circuits, it seems likely that this is indeed the case. We therefore propose that a generalizable function of activityinduced transcription in neural circuits lies in the activity-induced normalization of E/I-ratio and control over FRH to thereby counterbalance other forms of experience-dependent cellular-synaptic plasticity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies in rodent models have shown that NPAS4 has a neuroprotective role in cerebral ischemia and epilepsy [ 54 ]. Other animal models have indicated that NPAS4 could have a role in fear memory, anxiety, social- and depressive-like behavior [ 55 ] and Npas4 knockout mice display social anxiety, hyperactivity, memory and learning deficits [ 49 , 56 , 57 ]. NPAS4 deficiency in mice results in an increase in activated microglia and astrocytes as well as increased protein levels of IL-6 and TNF-α after stroke [ 54 ].…”
Section: Discussionmentioning
confidence: 99%